1997
DOI: 10.1080/02626669709492022
|View full text |Cite
|
Sign up to set email alerts
|

A worldwide comparison of regional flood estimation methods and climate

Abstract: A summary of the results of regional flood frequency analyses that have been carried out in many tropical and sub-tropical countries is presented. The results provide a set of flood estimation methods which should be of immediate usefulness in practical applications, bearing in mind the errors of generalization. By defining the representative values of the mean annual flood and of the flood frequency curves for each region, an attempt has been made to develop relationships between the methods and climatic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 13 publications
(16 reference statements)
5
64
0
Order By: Relevance
“…To compare the results from this study with similar OLS models reported in the literature by van Bladeren (1993), Mkhandi and Kachroo (1997) and Meigh et al (1997),the R 2 statistic was calculated for the OLS models.…”
Section: Applicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…To compare the results from this study with similar OLS models reported in the literature by van Bladeren (1993), Mkhandi and Kachroo (1997) and Meigh et al (1997),the R 2 statistic was calculated for the OLS models.…”
Section: Applicationsmentioning
confidence: 99%
“…Based on the previous studies by Meigh et al (1997) and Mkhandi and Kachroo (1997) and similar studies from other parts of the world, e.g. NERC (1975), AREA is the single most important variable and should always be included in the models.…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations